Illegal Gold Mining: A Systematic Literature Review from an Environmental Policy Perspective - Hatika, Rindi Genesa; Frinaldi, Aldri; Lanin, Dasman; Rembrandt, Rembrandt; Umar, Genius; Dewata, Indang; Audia, Washilla (Science and Environmental Journal for Postgraduate, 2025)
This systematic literature review analyzes the complexity of illegal gold mining (ASGM) from an environmental policy perspective through a review of 53 selected scientific publications (2000-2025). The results reveal that ASGM is the largest source of global mercury pollution, contributing 37% of anthropogenic emissions, which triggers environmental and health crises through bioaccumulation and biomagnification mechanisms in the food chain. Regulatory frameworks exist in Indonesia, such as the Minerba Law, the PPLH Law, the RAN PPM, and the ratification of the Minamata Convention. However, the main findings of this study identify a significant implementation gap between policy and practice in the field, caused by weak law enforcement, structural corruption, suboptimal inter-agency coordination, and the lack of viable technological and economic alternatives for communities. The root of the problem lies in a governance deficit, where a command-and-control approach fails to address the reality of ASGM as an economic lifeline for marginalized communities. Therefore, a sustainable solution requires a paradigm shift towards inclusive governance that integrates guided formalization, alternative economic empowerment, and a supply-chain approach to disrupt the distribution of illegal mercury.